The Impact Of Student Learning Independence On The Learning Outcomes Of Class X Students of SMK Al-Bukhori Rantauprapat - Amin Harahap (CV. AFDIFAL MAJU BERKAH, 2024)
The benchmark in determining the level of success of students in knowing and understanding a lesson is one of them with learning outcomes. Each student has different characteristics and learning spirit. Someone with independence learns more initiative and does not depend on others to solve the problems they face. In this study aims to examine the effect of learning independence on the learning outcomes of mathematics students in Class XI vocational school students. The study was conducted by survey method in one of the private vocational schools in Sleman Regency. This study examines the relationship between student learning independence and student learning outcomes. After testing the hypothesis shows that there is an influence between the independence of student learning on student math learning outcomes. The magnitude of the effect of student independence on student learning outcomes is 74% and 26% influenced by other variables.